CLXII years of creation of the National University of the Altiplano de Puno - Espezúa Salmón, Boris (2018)
The editorial committee of the High Andean Research Journal of the National University of the Altiplano of Puno (UNAP), will publish in this edition the speech given by Dr. Boris Epezua Salmón, Dean of the Faculty of Legal and Political Sciences, on the occasion of Celebrated the UNAP CLXII (162) years of creation. The committee wishes to highlight the years of trajectory of the UNAP in the construction of bridges of encounter between intelligence and reflection; teaching and learning; Investigation and debate of positions among others. All of them converge in the confrontation of ideas to identify problems and tend to contribute to their solution before imposing and submitting. The scenarios, referred in part, have been taken to external academic critics for evaluation in order to convert their positions into science if the evaluation was positive. The Editor of the RIA UNA-Puno